Public Participation in Policy Making: Sentiment Analysis of TAPERA Policy on Twitter - Rulandari, Novianita (Ilomata International Journal of Social Science, 2024)
The implementation of the TAPERA policy, an Indonesian government initiative designed to improve access to affordable housing through mandatory savings, has generated significant public debate, particularly on social media platforms like Twitter. This research analyzes public sentiment towards TAPERA on Twitter, focusing on the reactions and concerns of the community in response to the policy. Utilizing sentiment analysis and thematic analysis of tweets, this study identifies predominant negative sentiment and critical issues such as financial burden, transparency, and policy effectiveness. The findings reveal widespread dissatisfaction with the contribution requirements, organized public protests, and the influential role of social media in shaping public discourse. The results underscore the importance of incorporating diverse perspectives into policy development to enhance legitimacy and effectiveness. The research highlights the need for more inclusive and adaptive public participation strategies in the policy-making process. These insights contribute to the broader understanding of public participation theory and its application in digital contexts.